Incorporating Technology In Teaching: An Analysis Of Junior High School English Teacher Proficiency Based On Bloom's Digital Taxonomy Framework - Mahendra, Made Wahyu; Sarsini, Kadek Jeniari; Suhardiana, I Putu Andre (STKIP CITRA BAKTI, 2024)
This research aimed to reveal the extent of the proficiency level of Bloom’s Digital Taxonomy (BDT) Junior High School English Teachers and examined the factors that influenced English Teachers' Proficiency in integrating technology into instruction based on Bloom's Digital Taxonomy. Information and Communication Technology (ICT) was increasingly important in improving the learning process. This research used a mixed methods approach that combined a quantitative approach, namely a questionnaire, and a qualitative approach consisting of interviews, observations, and document analysis was gather comprehensive insights into teachers' skills in integrated Technology Pedagogy Content Knowledge (TPACK) into ELT. This research used stratified Cluster Random Sampling to determine the regions and English teachers who participated in this research. Data was obtained from a quantitative approach by distributing questionnaires to all Junior High Schools throughout North Denpasar to find out the results of the highest and lowest scores using Descriptive Statistical Analysis techniques with a total of 28 teachers who filled out the questionnaire. Then it was clarified using qualitative observations and interviews with small numbers of 2 English teachers from 2 different Schools who got high and low scores. The finding of this study is that the level of teacher proficiency is at level C3 and teacher proficiency factors are caused by external and internal factors. For further research, other researchers can explore the same study but with a larger sample take other regencies and investigate ELT from kindergartens or early preschool